Long Non-Coding RNAs in Infection Biology - Scaria, Vinod; Pasha, Ayesha (Frontiers in Genetics, 2013)
Long non-coding RNA have emerged as an increasingly well studied subset of non-coding RNAs (ncRNAs) following their recent discovery in a number of organisms including humans and characterization of their functional and regulatory roles in variety of distinct cellular mechanisms. The recent annotations of long noncoding RNAs in humans peg their numbers as similar to protein-coding genes. However, despite the rapid advancements in the field the functional characterization and biological roles of most of the long noncoding RNAs still remain unidentified, although some candidate long noncoding RNAs have been extensively studied for their roles in cancers and biological phenomena such as X-inactivation and epigenetic regulation of genes. A number of recent reports suggest an exciting possibility of long noncoding RNAs mediating host-response and immune function, suggesting an elaborate network of regulatory interactions mediated through ncRNAs in infection. The present role of long noncoding RNAs in host-pathogen cross talk is limited to a handful of mechanistically distinct examples. The current commentary chronicles the findings of these reports on the role of long noncoding RNAs in infection biology and further highlights the bottlenecks and future directions towards understanding the biological significance of the role of long noncoding RNAs in infection biology.